The Impact Of Audit Fee, Auditor Switching, Workload And Auditor Specialization On Audit Quality - averina, Putri; Hastuti, Theresia Dwi (Jurnal Akuntansi Indonesia, 2024)
During the research period from 2020 to 2022, this study was conducted to assess the impact of audit fees, auditor changes, workload, and auditor expertise on audit quality in financial sector companies listed on the Indonesia Stock Exchange (IDX). The number of companies in the study population was 314 (103 companies in 2020, 105 companies in 2021, and 106 companies in 2022). The purposive sampling method was used to select a sample of companies to be analyzed, with a total sample of 145 companies. In data analysis, this study applies a quantitative approach using logistic regression to test the validity of the regression, model fit, coefficient of determination, and research hypotheses. The results showed that audit fees and auditor expertise have a positive and significant effect on audit quality, while workload has a negative and significant model effect on audit quality. Auditor turnover is not proven to have a significant effect on audit quality. This research is expected to make an important contribution in the effort to improve audit quality by understanding more deeply the factors that affect such quality.keywords: Auditor Switching, Audit Fee, Auditor Specialization, Audit Quality, Workload